Effect of MPL Properties on Temperature and Liquid Water Distribution in a GDL. (24th August 2017) - Hashimura, Sota; Minami, Ryotaro; Tamada, Yusuke; Hasegawa, Noriyoshi; Araki, Takuto
Abstract : Management of heat and liquid water transport is important for further improvement of PEMFC performance. In this study, the effect of MPL properties on temperature and liquid water distribution was investigated. An X-ray CT apparatus was used for visualizing the liquid water in the GDL, and Au - Ni thin film thermocouples with a thickness of about 9 μm were fabricated using MEMS technology and used for the temperature measurement.